2018
DOI: 10.1002/jssc.201701008
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the clean‐up efficiency of the solid‐phase extraction of rosemary extracts: Application of full‐factorial design in hyphenation with Gaussian peak fit function

Abstract: We present a novel method for the quantitative determination of the clean-up efficiency to provide a calculated parameter for peak purity through iterative fitting in conjunction with design of experiments. Rosemary extracts were used and analyzed before and after solid-phase extraction using a self-fabricated mixed-mode sorbent based on poly(N-vinylimidazole/ethylene glycol dimethacrylate). Optimization was performed by variation of washing steps using a full three-level factorial design and response surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In this work, we focused on the development of a simple sample preparation procedure using SPE. Previous studies successfully showed that implication of weak anion-exchange-functionalized materials demonstrate high potential for isolation and clean-up of crude plant extracts [24,25]. After addition of HIS onto the present polymer backbone, the carboxy and imidazole functionalities remain free for interaction with molecules in solution.…”
Section: Clean-up and Analysis Of Tea Samplesmentioning
confidence: 97%
See 1 more Smart Citation
“…In this work, we focused on the development of a simple sample preparation procedure using SPE. Previous studies successfully showed that implication of weak anion-exchange-functionalized materials demonstrate high potential for isolation and clean-up of crude plant extracts [24,25]. After addition of HIS onto the present polymer backbone, the carboxy and imidazole functionalities remain free for interaction with molecules in solution.…”
Section: Clean-up and Analysis Of Tea Samplesmentioning
confidence: 97%
“…These materials are typically crosslinked with DVB leading to a hydrophobic backbone. However, previous studies demonstrated that sorbents crosslinked with EGDMA as hydrophilic compound also exhibit excellent results for application with plant extracts [24,25]. The functional modifier HIS was chosen as it contains anionic (imidazole) and cationic (carboxylic acid) ion-exchange moieties.…”
Section: Polymer Composition and Characterizationmentioning
confidence: 99%
“…Strong emphasis is being put there on the method development and optimization. 23,25 What is rather unique, this unit puts a fair share of its attention into physicochemical and theoretical support of its analytical activity. 26,27 This is an essential aid securing a broader and deeper perspective, and providing an unmatched balance in the available scientific resource.…”
Section: The Need For Comprehensive Research and Developmentmentioning
confidence: 99%
“…Meischl et al have applied the full-factorial design in spelling with the Gaussian peak fitting function to determine the cleaning efficiency of solid-phase extraction of rosemary extracts [23]. Melo et al, the effect of Portland cement inclusions in hybrid glass fibre reinforced composites based on a full-factorial design [24].…”
Section: Introductionmentioning
confidence: 99%